In the absence of viceroys: the political nature of the alter ego under the interim government of the Royal Audience of Lima (1672-1674) - Jiménez Castillo, Juan (2020)
The death of Viceroy Conde de Lemos, and the subsequent interim rule of the Royal Audience of Lima, caused significant disruption in the Viceroyalty of Peru until the arrival of the new Viceroy, don Baltasar de la Cueva, Conde de Castellar. This article examines the governance issues raised by the Viceroy’s absence; and studies the evolving nature of viceroyal politics, as reflected by developments during the interim period. Crucially, the latter occurred at a time of change in the Spanish Monarchy, with implications for the composition and governance of viceroyal domains. The working hypothesis is that the figure of the viceroy played an important role in preserving order and concentrating political authority; and that the latter diluted during interim governments, resulting in uncertainty and a considerable power vacuum.